2022
DOI: 10.1021/acs.joc.2c00956
|View full text |Cite
|
Sign up to set email alerts
|

Cyanine-Functionalized 2,2′-Bipyridine Compounds for Photocatalytic Cancer Therapy

Abstract: Recently, interest has been given to developing photocatalytic anticancer drugs. This area of research is dominated by metal complexes. Here, we report the potential of lysosome/mitochondria targeting cyanine appended bipyridine compounds as the organic photocatalytic anticancer agents. The organocatalyst (bpyPCN) not only exhibits light-induced NADH oxidation but also generates intracellular ROS to demonstrate anticancer activity. This is the first example of organic compound induced catalytic NADH photo-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…1a-c) are: (a) the 4,4 0 -disubstituted 2,2 0 -bipyridyl group is excellent as a chelating ligand and is used in the synthesis of metallodendrimers for various theranostics applications. 11 For instance, rutheniumbased metallodendrimers have been reported as sensitizers in photodynamic therapy, imaging, and sensing applications. 12 Ruthenium-based metallodendrimers are also known to exhibit anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…1a-c) are: (a) the 4,4 0 -disubstituted 2,2 0 -bipyridyl group is excellent as a chelating ligand and is used in the synthesis of metallodendrimers for various theranostics applications. 11 For instance, rutheniumbased metallodendrimers have been reported as sensitizers in photodynamic therapy, imaging, and sensing applications. 12 Ruthenium-based metallodendrimers are also known to exhibit anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in photoactivated cancer therapy, controlled ROS generation has been used to selectively destroy cancer cells while sparing healthy ones . ROS are reported to damage cancer cells by primarily damaging their DNA, proteins, and cell membranes, ultimately triggering apoptosis or necrosis. In photocatalytic cancer therapy, the photoresponsive metal complexes are reported to produce H 2 O 2 , OH • , and O 2 •– (as the byproducts of NADH oxidation) in addition to 1 O 2 (via a type II energy transfer pathway). The encouraging photophysical properties, DFT calculation data, and enhanced light-triggered cytotoxicity indicated that Ru1 – Ru3 could have a notable ROS generation tendency. To examine the 1 O 2 production efficiency of Ru1 – Ru3 , 9,10-diphenyl anthracene (DPA) has been used.…”
Section: Resultsmentioning
confidence: 99%
“…10 M deaths in 2020) and it is badly affecting the global health index . Primarily, Pt-based anticancer drugs have been employed as chemotherapeutics in combating this disease. However, their low tumor selectivity, adverse side effects, and acquired drug resistance have led to new initiatives toward developing better chemotherapeutic agents and advanced cancer therapies with reduced side effects, better tumor selectivity, and enhanced cytotoxicity. , Recently, a new type of photoactivated cancer therapy termed “photocatalytic cancer therapy” has arisen as a potential non-invasive alternative to the current cancer therapies. In photocatalytic cancer therapy, a photosensitive drug molecule is exposed to a certain wavelength of light to induce cytotoxicity via in-cell catalytic reactions and the production of reactive oxygen species (ROS). The in-cell catalytic reactions (such as NADH/NAD­(P)­H oxidation) and ROS generation are ultimately reported to perturb energy metabolism and redox state in cancer cells selectively. , These further disrupt cell signaling cascades and/or modify gene expression regulation, ultimately causing tumor cell damage. This novel concept, photocatalytic cancer therapy, has shown promising results in overcoming cisplatin resistance with high tumor selectivity both in vivo and in vitro . The advantages of photocatalytic cancer drug development could be (i) low to extremely low drug dose, helpful to avoid the toxicity of metal (in the case of metal-based photocatalytic anticancer agents), (ii) selective activation of the drug at the specified tumor site, helpful to reduce drug’s side effects, and (iii) overcoming current drug resistance issues by multifunctional and multitargeting anticancer mechanism. , …”
Section: Introductionmentioning
confidence: 99%
“…The signicant PDT performance was ascribed to its excellent ability for 1 O 2 generation and photocatalytic NADH oxidation. 138 To render the absorption of photocatalysts for photoredox catalysis in the NIR spectral range, Kim et al conjugated a BODIPY moiety to erlotinib (ER, an FDA-approved tyrosine kinase inhibitor) to obtain a photocatalyst (CatER) (Fig. 18a).…”
Section: Organic Metal-free Photocatalystsmentioning
confidence: 99%